Multitargeting nature of muscarinic orthosteric agonists and antagonists - Myslivecek, Jaromir (Frontiers in Physiology, 2022)
Muscarinic receptors (mAChRs) are typical members of the G protein-coupled receptor (GPCR) family and exist in five subtypes from M1 to M5. Muscarinic receptor subtypes do not sufficiently differ in affinity to orthosteric antagonists or agonists; therefore, the analysis of receptor subtypes is complicated, and misinterpretations can occur. Usually, when researchers mainly specialized in CNS and peripheral functions and aim to study mAChR involvement in behavior, learning, spinal locomotor networks, biological rhythms, cardiovascular physiology, bronchoconstriction, gastrointestinal tract functions, schizophrenia, and Parkinson’s disease, they use orthosteric ligands and they do not use allosteric ligands. Moreover, they usually rely on manufacturers' claims that could be misleading. This review aimed to call the attention of researchers not deeply focused on mAChR pharmacology to this fact. Importantly, limited selective binding is not only a property of mAChRs but is a general attribute of most neurotransmitter receptors. In this review, we want to give an overview of the most common off-targets for established mAChR ligands. In this context, an important point is a mention the tremendous knowledge gap on off-targets for novel compounds compared to very well-established ligands. Therefore, we will summarize reported affinities and give an outline of strategies to investigate the subtype's function, thereby avoiding ambiguous results. Despite that, the multitargeting nature of drugs acting also on mAChR could be an advantage when treating such diseases as schizophrenia. Antipsychotics are a perfect example of a multitargeting advantage in treatment. A promising strategy is the use of allosteric ligands, although some of these ligands have also been shown to exhibit limited selectivity. Another new direction in the development of muscarinic selective ligands is functionally selective and biased agonists. The possible selective ligands, usually allosteric, will also be listed. To overcome the limited selectivity of orthosteric ligands, the recommended process is to carefully examine the presence of respective subtypes in specific tissues via knockout studies, carefully apply “specific” agonists/antagonists at appropriate concentrations and then calculate the probability of a specific subtype involvement in specific functions. This could help interested researchers aiming to study the central nervous system functions mediated by the muscarinic receptor.